Do Analysts Understand the Valuation Implications of Accounting Conservatism when Forecasting Target Prices? - KIM, Jae Bum (Institutional Knowledge at Singapore Management University, 2012)
Conservatism in earnings does not have a direct impact on the present value of future cash flows. This paper examines whether financial analysts correctly undo the effect of accounting conservatism incorporated in their own earnings forecasts in arriving at their target price forecasts. Based on prior findings, we consider alternative valuation models/heuristics that may be used by analysts to estimate target prices, e.g. the forward P/E and the PEG ratio. Our evidence suggests that analysts fail to fully undo the effect of accounting conservatism embedded in their forecasts of earnings and earnings growth when estimating their target price forecasts. More sophisticated analysts undo the effect of conservatism to a greater extent than other analysts, although their target price forecasts also exhibit conservatism-induced bias. In contrast, the market on average appears to correctly unravel the conservatism in future earnings when pricing securities. However, for extreme levels of conservatism, our evidence suggests that the under/over-statement of target prices leads to a distortion of market prices.